Combined Effects of Aircraft, Rail, and Road Traffic Noise on Total Noise Annoyance—A Cross-Sectional Study in Innsbruck - Lechner, Christoph (Int J Environ Res Public Health, 2019)
Noise legislation in Austria does not provide an assessment of the cumulative effect of noise from different sources. The desire of citizens for a total noise assessment is getting stronger. Within the pilot project “Gesamtlärmbetrachtung” (Total Noise Investigation) Innsbruck, data from 1031 face-to-face interviews were correlated with exposure data from road, rail and air traffic noise. The interviews were selected in clusters according to the exposure combinations of these three sources. In addition to exposure-response relationships, it has also been found that the annoyance response to air and rail traffic noise is independent of the background noise from road traffic. The total noise annoyance response shows a cumulative effect in each source considered. From the source specific exposure-response relationships, a total noise assessment model based on the annoyance equivalents model was developed. This model is more suitable than the dominant source model and thus also considerable for legal application.